Digital Life and Youth Well-being, Social Connectedness, Empathy, and Narcissism - James, Carrie; Davis, Katie; Charmaraman, Linda; Konrath, Sara; Slovak, Petr; Weinstein, Emily; Yarosh, Lana (Pediatrics (Evanston), 2017)
Youth well-being, social connectedness, and personality traits, such as empathy and narcissism, are at the crux of concerns often raised about the impacts of digital life. Understanding known impacts, and research gaps, in these areas is an important first step toward supporting media use that contributes positively to youth's happiness, life satisfaction, and prosocial attitudes and behaviors. By examining existing work addressing these issues across domains, we found that a complex interplay of individual factors, type of digital media engagement, and experiences in media contexts informs outcomes related to well-being, social connectedness, empathy, and narcissism. We argue that further research is needed to uncover how, where, when, and for whom digital media practices support positive well-being and social connectedness outcomes. Specifically, research needs to move beyond correlational studies to uncover causal connections between traits like narcissism and media use. Longitudinal studies are also needed to explore patterns of media use over time and related impacts. Further research is needed to explore how specific technologies can be designed to support positive well-being, social outcomes, and prosocial personality traits. Finally, research is needed regarding parenting, educational practices, and policies that support positive digital media use and related outcomes. Although existing research suggests that digital life has mixed potentials and effects for well-being, social connectedness, empathy, and narcissism, we provide recommendations for clinicians, policy makers, and educators in partnering with caregivers and youth to support media use that promotes positive outcomes in these areas.